SERANGGA YANG TERDAPAT PADA PHYTOTELMATA (Nepenthes mirabilis DAN Nepenthes ampullaria) DI HUTAN PENDIDIKAN DAN PENELITIAN BIOLOGI UNIVERSITAS ANDALAS, PADANG - Hanifa, Eka Widya; Dahelmi, Dahelmi; Mairawita, Mairawita (Metamorfosa: Journal of Biological Sciences, 2017)
This research aimed to inventory the insects in pitcher plant ( Nepenthes mirabilis and Nepenthes ampularia ) found in the Biological Education and Research Forest of Andalas University, Padang. had been conducted manually from April to May 2015. Fourteen species which are belong to three orders namely Diptera, Hymenoptera and Isoptera were collected, which the most genera being sampled was Hymenoptera (10 species), followes by Diptera (3 species) and Isoptera (1 species).The highest number species collected (7 species) was belong to the family of Formicidae, then followed by Culicidae (3 species), and 1 species each for Vespidae, Ichneumonidae, and Termitidae. Two species which have the high number of individual collected were Tripteroides ( Rachionotomyia ) aranoides (473 individuals) and Topomyia sp. (216 individuals).
Keywords: Pyhtotelmata, Nepenthes, insecta